2021
DOI: 10.1177/0748233721989896
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophage-derived TGF-β1 on SiO2-induced pulmonary fibrosis: A review

Abstract: Silicosis is an occupational fibrotic lung disease caused by inhaling large amounts of crystalline silica dust. Transforming growth factor-β1 (TGF-β1), which is secreted from macrophages, has an important role in the development of this disease. Macrophages can recognize and capture silicon dust, undergo M2 polarization, synthesize TGF-β1 precursors, and secrete them out of the cell where they are activated. Activated TGF-β1 induces cells from different sources, transforming them into myofibroblasts through au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…The results suggest that TGF-b1 synthesis and secretion in macrophages partly depend on TIM-4, and MMPs may be mediated by other factors. After being secreted out of the macrophages, the TGF-b1 could bind to TGF-b1 receptors on epithelial cells and promote EMT through TGF-b1/Smad pathway (52).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that TGF-b1 synthesis and secretion in macrophages partly depend on TIM-4, and MMPs may be mediated by other factors. After being secreted out of the macrophages, the TGF-b1 could bind to TGF-b1 receptors on epithelial cells and promote EMT through TGF-b1/Smad pathway (52).…”
Section: Discussionmentioning
confidence: 99%
“…And in the lung repair process, M2 macrophages are responsible for the regulation of fibrogenesis, which aggravates the progression of pulmonary fibrosis 35,36 . M2 macrophages can secrete excess TGF-β to enhance the proliferation and differentiation of lung fibroblasts and thus facilitate the progression of pulmonary fibrosis 37 . Moreover, a previous study has revealed that PM exposure could trigger epithelial-mesenchymal transition (EMT) in alveolar epithelial cells 38 .…”
Section: Pms and Pulmonary Fibrosismentioning
confidence: 99%
“…The pathogenesis of acute silicosis remains unclear. Recent studies suggested that alveolar macrophages, the first line of defense against invading lungs (Balhara and Gounni, 2012), have an important role in the development of silicosis (Zhang et al, 2019b(Zhang et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of acute silicosis remains unclear. Recent studies suggested that alveolar macrophages, the first line of defense against invading lungs (Balhara and Gounni, 2012), have an important role in the development of silicosis (Zhang et al, 2019b, 2021). Two hallmarks of macrophages are diversity and plasticity due to their phenotype responses to a variety of different stimuli of the tissue microenvironment (Gordon and Plűddemann, 2013; Arora et al, 2018).…”
Section: Introductionmentioning
confidence: 99%